Effectiveness of Mg(OH)2/γ-Al2O3 Catalysts on Catalytic Cracking Process - Rasyid, Rismawati; Wiyani, Lastri; Ramadhan, Alif Qayyum; Ahmad, Muhammad Aslam (Fakultas Teknologi Industri - Universitas Muslim Indonesia, 2024)
Petroleum is one of the energy sources that currently has very wide uses. In addition to the fact that petroleum is a non-renewable resource, the use of fuel oil has also affected emission levels. Biofuel is an alternative fuel in solid, liquid or gas form that can be obtained from animals, plants, or agricultural waste. The process of making biofuel can be done by several methods, namely by thermal cracking, hydrocracking, and catalytic cracking. Thermal cracking is a simple process where heat is used to cut long hydrocarbon chains. Catalytic cracking is the process of breaking hydrocarbon chains using a catalyst. This study aims to determine the effect of Mg(OH)2/γ-Al2O3 catalyst (2 and 6)% and to determine the effect of the ratio of Mg(OH)2/γ-Al2O3 catalyst (1, 2, 3 and 4)% on the yield and selectivity of biofuel products from catalytic cracking of palm oil. The process of making biofuel through catalytic cracking process using Mg(OH)2/ γ –Al2O3 catalyst as much as 1% of the volume of material with a temperature of 370℃ on a hotplate magnetic stirrer and reactor for ±3 hours. The biofuel results were analyzed by Gas Chromatography Mass Spectrophotometry (GCMS). The highest biogasoline was obtained using Mg(OH)2/γ-Al2O3 catalyst 2% with a ratio of 2% which was 16.6%. While the highest biodiesel was obtained using Mg(OH)2/γ-Al2O3 catalyst 6% with a ratio of 2% which was 42.7%.